Cardiac computed tomography beyond anatomical coronary artery disease assessment: A contemporary review - Vori, Ira; Handari, Saskia Dyah (Universitas Brawijaya, 2025)
Cardiac computed tomography (CT) has undergone a remarkable transformation over the past two decades, evolving from a purely anatomical imaging modality to a comprehensive cardiac assessment tool. This review examines recent technological advancements and expanded clinical applications of cardiac CT. Contemporary systems, equipped with dual-energy imaging, wide-detector arrays, and sophisticated reconstruction algorithms, now enable functional assessment through myocardial perfusion imaging and CT-derived fractional flow reserve (CT-FFR), alongside advanced plaque characterization. Technical developments have improved temporal and spatial resolution while optimizing radiation exposure through refined dose management protocols. The integration of anatomical and functional data has proven particularly valuable in triple rule out at emergency department and also a guide for revascularization decisions, as physiological significance often supersedes anatomical severity in clinical decision-making. Additionally, cardiac CT has emerged as an essential tool in pre-procedural planning for structural heart interventions, including transcatheter aortic valve replacement, left atrial appendage (LAA) closure, and mitral valve (MV) interventions. The modality also demonstrates significant utility in electrophysiology applications, particularly in planning pulmonary vein isolation procedures. Recent guidelines from major cardiovascular societies have incorporated these advances, positioning cardiac CT as a first-line diagnostic tool for stable chest pain and a cost-effective gatekeeper for invasive procedures. Future directions include expanded applications in quantitative plaque assessment, artificial intelligence integration, and personalized risk stratification, promising to further enhance the role of cardiac CT in clinical practice.